Should coaches use personality assessments in the talent identification process? A 15 year predictive study on professional hockey players. - Gee, C. J.; John, C. M.; King, J. F. (International Journal of Coaching Science, 2010)
Making an accurate and valid prediction about an athlete's long term success in professional sport is likely a difficult aspect of a professional coach's role. Therefore, to aid them in this evaluative process coaches routinely employ a battery of tests, all of which are intended to inform their eventual selection decision. To date however, personality inventories have yet to become common place within this evaluative process; and thus, their predictive utility within the talent identification process has not yet been adequately tested (Aidman, 2007). Those research efforts that have been concerned with personality's role in predicting athletic success have been overwhelmingly cross-sectional and descriptive in nature, and therefore do not mirror the applied use (e.g., longitudinal prediction) of these instruments by coaches. Consequently, the purpose of the current investigation was to address these previous limitations by employing a normative measure of personality (SportsPro™; Marshall, 1979) and assessing its relationship to athletic performance over a 15 year time period. Potential draft choices of a Canadian National Hockey League team (N=124) were profiled prior to the 1991-92 entry draft and were followed until the end of the 2005-06 NHL season. The proposed selection model was found to be a significant predictor of a player's total NHL goals, NHL assists, and their overall NHL points. Overall, when performance is assessed longitudinally within a relatively homogenous sample of athletes, personality measures appear to add to a coach's ability to predict an athlete's longitudinal athletic attainment.